The influence of professional ethics, competency, integrity, skeptism and experience on audit quality with independence and risk based audit as intervening variables and artificial intellegance audit as a moderation variable at financial and development supervisory board in East Kalimantan - Muslimin, Muslimin; Ratnawati, Tri; Riyadi, Slamet (Edelweiss Applied Science and Technology, 2024)
Professional ethics has a positive and significant effect on independence. Professional ethics has a positive and significant effect on Risk Based Audit. Professional ethics has a negative and insignificant effect on audit quality. Competence has a positive and significant effect on independence. Competence has a positive and significant effect on risk based audit. Competence has a positive and significant effect on audit quality. Integrity has a positive and significant effect on independence. Experience has a positive and significant effect on independence. Experience has a positive and significant effect on risk based audits . Experience has a positive and insignificant effect on audit quality. Independence has a positive and significant effect on audit quality. Risk based audit has a positive and significant effect on audit quality. Audit Artificial Intelligence has a positive but not significant moderating effect on (Y1) Independence on (Y3) Audit Quality. Artificial Intelligence Audit has a positive but not significant moderating effect on (Y2) Risk Based Audit on (Y3) Audit Quality. Researchers provide advice to the East Kalimantan BPKP Representative to always maintain professional ethics, improve their competence, maintain integrity as an auditor, increase skepticism and increase their experience in auditing and be able to maintain their independence and be able to control risk-based audits.